Procedura notyfikacji suplementów diety, czyli o potrzebie nowelizacji ustawy z 25 sierpnia 2006 r. o bezpieczeństwie żywności i żywienia - Szymecka-Wesołowska, Agnieszka (Wydawnictwo Naukowe UAM, 2014)
Notification procedure of dietary supplements – the need for amendments to the law of 25 August 2006 on food and nutrition safety S u m m a r y The aim of these deliberations is to identify the main shortcomings of the currently binding notification procedure of dietary supplements, and its legal and economic effects in practice, affecting not only Polish entrepreneurs but consumers as well. These shortcomings include among other things the extent (scope) of the notification requirement, the clarification procedure conducted by the Main Sanitary Inspector, and, in particular, the form of its commencement and termination. They also include the absence of a regulation of giving notice of necessary corrections, and the form in which the whole procedure is to be completed. The remarks presented in the paper are briefly analysed from the legal point of view, and different opinions of administrative courts are compared. Concluding, the author confirms the view expressed earlier in the doctrine that the regulations governing the notification procedure with regards dietary supplements (as well as selected types of special purpose food and enriched food) set out in the Law on food and nutrition safety of 25 August 2006 must be amended. This need is justified not only because the current procedure requires improvement to serve entrepreneurs better, but also to ensure compliance of the Polish regulation with the European Union law.

La procedura di notifica per gli integratori alimentari, cioè sulla necessità della modifica della legge del 25 agosto del 2006 sulla sicurezza alimentare e degli alimenti R i a s s u n t o Lo scopo delle considerazioni è di indicare le principali lacune nella procedura di notifica in vigore e dei suoi effetti giuridici ed economici pratici, non solo dal punto di vista degli imprenditori, ma anche dei consumatori. Le lacune in questione riguardano tra l’altro la portata dell’obbligo di notifica, il procedimento di indagine formale svolto da parte del Principale Ispettore Sanitario, tra cui soprattutto le procedure di inizio e conclusione del procedura notyfikacji suplementów diety 175 procedimento, la mancante regolazione della questione di comunicazione correttiva e le forme di conclusione della procedura di notifica stessa. Le osservazioni presentate nell’articolo sono accompagnate da elementi di analisi giuridica comparata e dalle prese di posizione da parte dei tribunali amministrativi. In conclusione, l’autrice ribadisce la necessità segnalata già in dottrina di apportare modifiche alle regole giuridiche che regolano la procedura di notifica in materia di integratori alimentari (ma anche di alcuni tipi di prodotti alimentari destinati ad una alimentazione particolare e di alimenti arricchiti) contenuti nella legge del 25 agosto 2006 sulla sicurezza alimentare e degli alimenti. La modifica di queste regole è giustificata non solo dalla necessità di migliorare la procedura in discussione, auspicabile dal punto di vista degli imprenditori, ma anche per garantire la compatibilità delle regolazioni polacche con il diritto dell’Ue.